0826 Gender Differences in Sleep Knowledge of Community-Dwelling Older Adults. (27th May 2020) - Baldwin, C M; Link, D G; Coon, D W; Quan, S F
Abstract: Introduction: This work compares sleep knowledge of community-dwelling older adult men and women. Methods: Data were derived from a community-based sleep training program that assessed pre- and post-test knowledge of obstructive sleep apnea (OSA), Insomnia, short sleep duration (SSD), restless leg syndrome (RLS), circadian rhythm disorders (CRD), and drowsy driving (DD) on a 1 (none) to 5 (great deal of knowledge) Likert-like scale. Data were analyzed with frequencies for age, sex, and sources of sleep information, and ANOVA to determine gender differences using SPSS (V24) with significance set at p <.05. Results: Participants (N=158; 68% women) were 56 years and older residing in a retirement community. Pre-test means±standard deviations showed women versus men had greater knowledge of Insomnia (3.5±1.3 vs. 2.9±1.0, p =.004) whereas men showed more knowledge of DD (3.2±1.1 vs. 2.6±1.3, p =.01). A trend was noted for women to have greater knowledge of SSD (3.6±1.2 vs. 3.2±1.0, p =.05). Post-test ANOVA showed a further increase in Insomnia knowledge for women versus men (4.4±0.8 vs. 4.1±0.7, p =.04); however, overall pre/post-test scores for each of the sleep disorders across men and women increased significantly at the p <.001 level. Notably, more women to men reported accessing various resources for sleep information: newspapers/magazines (46:7), friends/family (29:9), the internet (25:11), TV (37:7), and physicians/nurses (45:20). Conclusion: Findings indicate, prior to sleep training, women have greater knowledge of insomnia and short sleep duration, while men have more knowledge of drowsy driving. Women's greater understanding of insomnia persists even after sleep training; however, pre- to post-test scores for both sexes across sleep disorders show significant learning outcomes. One possible reason for women's greater knowledge of insomnia and short sleep could be their greater likelihood to access information on health and healthy lifestyle factors, including sleep, as well as their greater health care utilization. Support: N/A